2024
DOI: 10.1039/d3ee03052k
|View full text |Cite
|
Sign up to set email alerts
|

A deformable complementary moisture and tribo energy harvester

Gwanho Kim,
Jae Won Lee,
Kaiying Zhao
et al.

Abstract: A deformable complementary energy harvester combining moisture-induced and triboelectric energy in a single cell is developed, offering mechanical resilience, high energy output, rapid capacitor charging, and potential in emergency guidance systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Numerous studies have reported materials with significant output power densities and provided valuable models for theoretical research. 7,10,53 However, achieving a trade-off between the selectivity and the permeability remains a challenge. In this study, hierarchical structures that facilitate rapid ion flow while maintaining high selectivity were constructed.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported materials with significant output power densities and provided valuable models for theoretical research. 7,10,53 However, achieving a trade-off between the selectivity and the permeability remains a challenge. In this study, hierarchical structures that facilitate rapid ion flow while maintaining high selectivity were constructed.…”
Section: Resultsmentioning
confidence: 99%
“…The directional movement of protons has occurred due to the moisture gradient that works similarly to GO, MoS 2 , etc. Recently, a moisture and triboelectric nanogenerator has been developed by Kim et al 103 using 2D Ti 3 C 2 T x /melamine foam; one-fifth of the active sample has been coated with an organoionic hydrogel, which supplies water and ions to the uncoated MXene. A single unit of this highly deformable energy harvester generates electric energy by absorbing moisture and triboelectricity.…”
Section: ■ Fundamentals Of Two-dimensional Transition Metal Dichalcog...mentioning
confidence: 99%
“…; a Ti 3 C 2 T x / melamine composite-based MEG generates power from moisture at 20−90% RH. 103 So, it is quite early to judge the best 2D materials for MEG Still, based on the few previously reported results, graphene QDs, GO/rGO composite, and GO fiber are the most efficient candidates for MEGs compared to other 2D materials. Hence, more exploration is still necessary to determine the best 2D materials for MEG applications.…”
Section: ■ Applicationsmentioning
confidence: 99%
See 1 more Smart Citation